2015
DOI: 10.1038/icb.2015.77
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 drives IRF6‐dependent IL‐23p19 expression and p19/EBI3 heterodimer formation in keratinocytes

Abstract: Interferon regulatory factor (IRF) family members impart cell-type specificity to toll-like receptor (TLR) signalling, and we recently identified a role for IRF6 in TLR2 signalling in epithelial cells. TLR3 has a well-characterized role in wound healing in the skin, and here, we examined TLR3-dependent IRF6 functions in human keratinocytes. Primary keratinocytes responded robustly to the TLR3 agonist poly(IC) with upregulation of mRNAs for interferon-β (IFN-β), the interleukin-12 (IL-12) family member IL-23p19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 53 publications
2
71
1
Order By: Relevance
“…In oral keratinocytes, IRF6 regulates Grainyhead-like 3 expression [57,58], which has been reported to directly regulate TGM1 transcription [59]. Thus, it is conceivable that TLR3-inducible TGM1 expression occurs via the IRF6-dependent pathway [18]. Finally, the importance of such responses in wound repair is highlighted by the observation that Tlr3 -/-mice exhibit chronic wounds and impaired re-epithelialization following acute UVB-irradiation [56].…”
Section: Skinmentioning
confidence: 93%
See 4 more Smart Citations
“…In oral keratinocytes, IRF6 regulates Grainyhead-like 3 expression [57,58], which has been reported to directly regulate TGM1 transcription [59]. Thus, it is conceivable that TLR3-inducible TGM1 expression occurs via the IRF6-dependent pathway [18]. Finally, the importance of such responses in wound repair is highlighted by the observation that Tlr3 -/-mice exhibit chronic wounds and impaired re-epithelialization following acute UVB-irradiation [56].…”
Section: Skinmentioning
confidence: 93%
“…Therefore, IRF6-mediated IFN- inhibition may enable a proliferative and reparative response in the skin. Intriguingly, we recently showed that poly(IC) selectively upregulates the expression of the IL-12 family genes IL-23p19 ( sub-unit) and Epstein-Barr virus induced 3 (EBI3) ( sub-unit) in keratinocytes, and that these two sub-units interact when co-expressed in cells [18]. This suggests that IL-23p19 and EBI3 may function as a novel IL-12 family cytokine.…”
Section: Skinmentioning
confidence: 99%
See 3 more Smart Citations